Muscle and cerebral oxygenation during cycling in chronic obstructive pulmonary disease: A scoping review. (16th February 2021) - Miles, Melissa; Rodrigues, Antenor; Tajali, Shirin; Xiong, Yijun; Orchanian-Cheff, Ani; Reid, W Darlene; Rozenberg, Dmitry
To synthesize evidence for prefrontal cortex (PFC), quadriceps, and respiratory muscle oxygenation using near-infrared spectroscopy (NIRS) during cycling in individuals with chronic obstructive pulmonary disease (COPD). A scoping review was performed searching databases (inception-August 2020): Ovid MEDLINE, EMBASE, Cochrane Systematic Reviews, Cochrane Central Register of Controlled Clinical Trials, CINAHL, SPORTDiscus and Pedro. The search focused on COPD, cycling, and NIRS outcomes. 29 studies (541 COPD participants) were included. Compared to healthy individuals (8 studies), COPD patients at lower cycling workloads had more rapid increases in vastus lateralis (VL) deoxygenated hemoglobin (HHb); lower increases in VL total hemoglobin (tHb) and blood flow; and lower muscle tissue saturation (StO2 ). Heliox and bronchodilators were associated with smaller and slower increases in VL HHb. Heliox increased VL and intercostal blood flow compared to room air and supplemental oxygen in COPD patients (1 study). PFC oxygenated hemoglobin (O2 Hb) increased in COPD individuals during cycling in 5 of 8 studies. Individuals with COPD and heart failure demonstrated worse VL and PFC NIRS outcomes compared to patients with only COPD—higher or more rapid increase in VL HHb and no change or decrease in PFC O2 Hb. Individuals with COPD present with a mismatch between muscle oxygen delivery and utilization, characterized by more rapid increase in VL HHb, lower muscle O2 Hb and lower muscle StO2 . PFC O2 Hb increases or tends to increase in individuals with COPD during exercise, but this relationship warrants further investigation. NIRS can be used to identify key deoxygenation thresholds during exercise to inform PFC and muscle oxygenation.